A diaphragm DEG mechanism with a segmented deformation space and its analysis and design - Takumi SANO; Kunitomo KIKUCHI; Kenji NAGASE (Nihon Kikai Gakkai ronbunshu, 2025)
This study concerns a diaphragm mechanism for the deformation (expansion/contraction) of dielectric elastomer generators (DEG). The DEG converts mechanical energy to electrical one owing to the capacitance change according to its deformation. One of the typical mechanisms for the deformation is a diaphragm mechanism, which utilizes the difference of fluid pressure to inflate a DEG sheet. Diaphragm mechanism devices have no moving part for deformation, and thus are expected to reduce the device size and maintenance frequency compared to mechanical ones employing moving parts. In the literature of the DEG diaphragm, free deformation of a circular membrane up to a hemisphere is often considered. However, the hemisphere deformation is usually far less than its maximum stretch coming from the material limit, and there is a possibility to improve the power generation efficiency. This paper proposes a new type of the DEG diaphragm mechanisms, which employs a segmented deformation space to increase the material stretch up to its maximum. The proposed device has cavities for deformation in its upper cover, and the sheet deforms along their walls. These cavities make the sheet deform like the folds in the stomach, and can increase the DEG surface area as desired. We first show that the voltage and energy increments per cycle by the DEG increase with respect to the area change ratio of the DEG sheet. The area change ratio for the proposed DEG diaphragm can be represented as a function of the numbers of segmentation, which is then utilized for the optimal design of the segmentation. The area change ratio can be continuous by introducing a protrusion in each cavity, which allows us to achieve the DEG stretch up to its maximum. Experimental results show the efficiency of the proposed mechanism.